Pembelajaran Masyarakat 5.0 Melalui Chanel Youtube - Adi Kurniawan , Ficky; Nakhma’ussolikhah; Muslimah (ISLAMICA, 2022)
The influence of individuals on lifestyle and the frequency of internet access affects attitudes, mindsets, paradigms and other actions on aspects of personal, social, study and career life. This change brings the individual into an individualist society. Lack of caring attitude towards other people and around the place of residence, one of the causes of this behavior include feeling comfortable when accessing YouTube. The purpose of this study is to increase understanding of the personal and social aspects. Technology is present as a tool or media to facilitate individuals in living their lives more effectively and efficiently. This type of research uses a qualitative approach to phenomenological design. Data collection techniques using observation, questionnaires and interviews. The results of this study explain that people in the technological era are still confused about the use of Android with various features. the ease of internet access has brought about a major change in lifestyle, thinking. Some people have a high level of understanding of the use of technology, namely by using it for online business, establishing communication, and learning and developing a career.